Histórias entrelaçadas: presença da dança na Escola de Educação Física da UFMG(1952-1977) - Marcos Antonio Almeida Campos (2007)
The aim of this study was to discuss the dance practice in the formation of Physical Education professors in the circunstances that had involved the School of Physical Education of the UFMG during the period that goes from 1952 to 1977. It is justified by the small production on the history of the dance in superior institutions of Physical Education and by the possibility of discussing the relationship of the man with representations that shows the dance as a practice typically feminine. This research tells the history of the School of Physical Education of the UFMG that in 1952 began its activities from the foundation of two institutions and one year later got together and started to undertake diverse actions searching for a bigger projection in the capital of Minas Gerais. After a period of great financial crisis it became an institution of the UFMG in 1969 having to submit to new functioning judgments, this fact generated a big tension between professors and university. The periodic Educação Física, the Internacional Journals, the PREMEM course, the construction of the new headquarters in Pampulha and the concourses for state professors are some themes in the history of this instituition. In the middle of this the dance appears as a practice for the students through the work of professors to diversify contents and teaching strategies of dance. It was a theme in classes of Rhythmic Gymnastics, Dances, Rhythmic and Recreation appearing in internal and external courses and events of the institution and presenting itself in various periods and spaces of the formation of Physical Education professors. The narrative is divided in four chapters and present important events in the history of the School of Physical Education of the UFMG in that period, allowing to show the context of the dance in circumstances of great changes. So a great amount of documentary sources such as written, oral and iconographic were mobilized, demanding a crossing of information to produce a version of the different ways that the dance was set in the School of Physical Education of the UFMG as well as in the formation of professors and in the professional practice of students in the first 25 years of existence of this institution.